Maternity Continuum Care Completion and Its Associated Factors in Northwest Ethiopia - Daniel Tsega; Melaku Admas; Asmare Talie; Tesfa Birlew Tsega; Molla Yigzaw Birhanu; Simegn Alemu; Belayneh Mengist (Journal of Pregnancy)
Background. Continuum care is a basic package approach for women to receive essential services throughout pregnancy, childbirth, and postpartum, and it is critical for women and their infants’ survival and well-being. Although it is an effective strategy for improving maternal and child health, it has not been implemented adequately in less developed countries, primarily in sub-Saharan Africa, including Ethiopia, where 55% of women have been dropped out from the continuum of care. Therefore, this study is aimed at assessing maternity continuum care completion and its associated factors within northwest Ethiopia, 2020. Materials and Methods. A community-based cross-sectional study design was considered among 504 women from March 10 to March 30, 2020, using pretested and structured questionnaires administered via face-to-face interviews. To select study participants, a simple random sampling technique was used. Data were coded, checked, and entered into EpiData software (V. 4.2), then transferred to SPSS (V. 25) for further analysis. A bivariable analysis with 95% CI was performed, and variables with P 0.25 during binary logistic regression were entered into a multivariable analysis to assess predictors’ independent effect. Results. About 177 (37.6%) women completed maternal continuum care. Women with secondary education and above (AOR=2.75, 95% CI 1.42-5.32), urban residence (AOR=2.45, 95% CI 1.35-4.45), using ambulance transport (AOR=3.96, 95% CI 2.19-7.19), mass media exposure (AOR=3.64, 95% CI 2.02-6.56), and distance from health facilities (AOR=3.22, 95% CI 1.84-5.63) showed significant positive associations with completion of maternity continuum care. Conclusion. However, a higher proportion of mothers completed the continuum of maternity care in the district than Ethiopian Demographic and Health Survey 2016 (9.1%); further interventions are compulsory to reach the acceptable level. Hence, comprehensive awareness-raising, education, and promotion activities at the community and health facility levels and empowering women in health care and decision-making backing to expand the completion of maternity continuum of care are necessary.